Sustainable consumption in tourism: an approach to its state of knowledge (2020)
Research on environmental practices has received increasing attention in the tourism’s area. However, a bibliographic review is needed to explore sustainable consumption practices in the sector. To this end, based on the use of the ATLAS.ti 9 software, a thematic analysis of 128 articles was carried out, the main objective of which is to examine the analyzes of sustainable consumption –good practices, consumer habits and public policies and environmental regulations–, its conflicts of application –by type of company– and its relationship with innovation (for example, the use of eco-technologies). In the results, the analysis shows that good practices have a positive association with innovation (0.72), which shows that the relationship is well established.